Analyses of Health Care Reforms in Uganda and Its Impact on Health Equity - Okech, Timothy C. (Issues and Development in Health Research Vol. 7, 2021)
Over the years, the Government of Uganda in collaboration with key stakeholders has initialed health policy reforms aimed at enhancing equity in health care. These including increasing access to health care, enhancing quality of care, efficiency in health care delivery and finally reduction in catastrophic health expenditures. The objective of the analysis was to synthesis the various health reforms that have been initiated and how they have affected health equity in the country. This report is based on a review of both published and unpublished reports from the government of Uganda, multilateral organizational reports including World Bank and World Health organization, commissioned studies by government and development partners. Notable findings include inequities due to limited supply of drugs and other pharmaceutical supplies, quality concerns and a lack of high impact interventions. Other findings include existence of cases of under-table payments, unsustainable out-of pocket payments which contribute towards high incidences of catastrophic health spending, dilapidated health infrastructure in many parts of the country, low morale among the health personnel, and low levels of spending by the government on health care. The reforms have however, contributed towards efficiency gains in terms of increased use of lower-level government facilities including health centers and concomitant reductions in the use of hospital services. The report recommends for increased investment in the health sector; systematic planning and implementation of policies by involving all key stakeholders; strengthening supply of essential medicines, rehabilitating of health infrastructure, provision of incentives to health personnel. Other recommendations include supporting the operations of community health insurance and other pre-payment schemes meant to caution the poor from health expenditure catastrophe. Similarly, political commitment in increasing government spending on health care in line with the Abuja Declaration of 2001 is recommended, while putting in place policies aimed at enhancing efficiency in health care delivery.